Optical fiber-based sensors as an experimental tool to assess the weft and warp yarn tension beam-to-roll in rapier weaving machines. Issue 7 (April 2020) - De Pauw, Ben; Berghmans, Francis; Thienpont, Hugo; Verdiere, Piet; Geernaert, Thomas
High cycle rates are important in commercial weaving machines to maximize productivity. Faster operation, however, can lead to higher tension on the yarns, which in turn increases the occurrence of yarn breakage and thus machine interruptions. Significant work has therefore been conducted to improve the many weaving machine components with the goal to attain higher production rates without increasing the yarn loads. Quantifying the impact of such improvements is not always possible using conventional, indirect measurement techniques. In addition, these techniques are limited to locations with sufficient access to the yarn to mount a sensor, typically between the warp beam and the first harness. In this paper, we show that the use of optical fiber-based sensors allows directly measuring the yarn tension in both the warp and weft directions in the region from the warp beam to the fabric rolls in rapier-type weaving machines. To do so, we replaced one warp and one weft yarn with an optical fiber equipped with strain sensors and measured strain throughout the subsequent weaving process. The small diameter of the optical fiber allowed minimizing our intrusion on the weaving operation. Our main observations are four-fold. Firstly, we demonstrated how the strain on the warp yarns evolves during the weaving cycle and we used this to focus on the beat-up phase for a low weaving resistance situation. Secondly, we monitored the warp yarn tension between the warp beam and the fabric rolls. Thirdly, we exploited the multiplexing capability of the optical fiber sensors to obtain a tension distribution along the width of the fabric in the weft direction between the reed to the fabric roll. Fourthly, we observed and identified the different phases of a yarn insertion (weft-wise) in a double rigid rapier machine.